Consumo da experiência em revistas brasileiras: Nova, Claudia, Boa Forma, Você S/A e Viagem e Turismo - Trindade, Thaís Hoehne Peres Polato (2010)
This research addresses the consumption of experience in magazine journalism. Experience , in global capitalism, is understood as a set of practices related to the daily lives of consumers and acts of knowing through the senses aspects that, in neoliberalism, become more closely linked to consumption/consumerism. We will determine to what extent these new relationships between experience and consumption affect and are affected by journalism and study the communication contracts proposed by writers to their readers, based on the importance of socially addressing the topic, since the media invest in the construction of identities in the contemporary world and expand the process of marketization of everyday life. We limited the scope of the study to the 2008 issues of the magazines Claudia, Nova, Boa Forma, Você S/A, and Viagem e Turismo. Our research question is posed as follows: in what ways have Brazilian targeted magazines adhered to the consumption of experience that marks global capitalism? This occurs at least at four levels: journalistic coverage of experience marketing events; appeal to experience; experience marketing conducted by the magazines themselves and consumption of experience. In our view, the latter is a step further in the modalization of the subject by the media because of its appeal to the reader s senses and action. Thus, it further contributes to expanding the phenomenon that has transformed aspects of human existence that had not yet become consumer products. In order to contextualize the topic, we worked with authors who deal with post-modernism, new capital values, and changes brought to communication, such as André Gorz, Giorgio Agamben, Zygmunt Bauman, Jeremy Rifkin, Muniz Sodré, Terry Eagleton, and David Harvey. For the preparation and analysis of the corpus, we take as a starting point the reflections on journalism, consumption, middle class, and theories of discourse by the authors Leandro Marshall, Isleide Fontenelle, Marcio Pochmann, Diana Barros, Vicente Pietroforte, José Luiz Aidar Prado, and Ernesto Laclau. Discourse analysis will be used to deconstruct the texts examined